2007
DOI: 10.1021/ja0677261
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Defects on the Electrical Characteristics of Mercury-Drop Junctions:  Self-Assembled Monolayers of n-Alkanethiolates on Rough and Smooth Silver

Abstract: This paper compares the structural and electrical characteristics of self-assembled monolayers (SAMs) of n-alkanethiolates, SCn (n = 10, 12, 14), on two types of silver substrates: one used as-deposited (AS-DEP) by an electron-beam evaporator, and one prepared using the method of template-stripping. Atomic force microscopy showed that the template-stripped (TS) silver surfaces were smoother and had larger grains than the AS-DEP surfaces, and reflectance-absorbance infrared spectroscopy showed that SAMs formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
407
5
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(422 citation statements)
references
References 73 publications
7
407
5
3
Order By: Relevance
“…25 The Ag TS electrodes have a lower surface roughness (root-meansquare roughness = 1.2 ± 0.1 nm measured over an area of 25 µm 2 ) than substrates used as-deposited by e-beam evaporation (AS-DEP, root-mean-square roughness = 5.2 ± 0.4 nm measured over an area of 25 µm 2 ). 25 The maximum grain size was ~1 µm 2 on the Hg top-electrode are required to obtain stable, non-shorting junctions). 25,53,54 We found that the shape and surface roughness of the cone-shaped tips depend on the operator.…”
Section: Experimental Designmentioning
confidence: 96%
See 3 more Smart Citations
“…25 The Ag TS electrodes have a lower surface roughness (root-meansquare roughness = 1.2 ± 0.1 nm measured over an area of 25 µm 2 ) than substrates used as-deposited by e-beam evaporation (AS-DEP, root-mean-square roughness = 5.2 ± 0.4 nm measured over an area of 25 µm 2 ). 25 The maximum grain size was ~1 µm 2 on the Hg top-electrode are required to obtain stable, non-shorting junctions). 25,53,54 We found that the shape and surface roughness of the cone-shaped tips depend on the operator.…”
Section: Experimental Designmentioning
confidence: 96%
“…2), thin-area defects cause a much greater deviation between the predicted and measured values of J than thick-area defects. 25 Thin-area defects lead to high observed values of J, and these anomalously high values of J can dominate the observed transport of charge through a junction to a disproportionate extent, relative to their area. By contrast, thick-area defects decrease the observed value of J, but only in (approximately) direct proportion to their area.…”
Section: (Or Vice Versa)mentioning
confidence: 97%
See 2 more Smart Citations
“…[96,132,133] To control both transport and dipole effects, it seems therefore best to start from a transport quality monolayer that passivates the surface chemically and electronically, and then add polar (or other functional) moieties that do not affect the integrity of the interface. [49,[134][135][136] …”
Section: Molecular Dipolementioning
confidence: 99%